A single phase 9-level inverter controlling based on Phase Lock Loop technique - Tipsuwanporn, V.; Charean, A.; Numsomran, A.; Phipek, K. (My University, 2012)
In this paper is presented the multilevel inverter which is controlled by Phase Lock Loop (PLL) controller in close-loop system. The multilevel inverter was multiplied voltage levels at output. The inner PLL controller was controlled by PI control in order to firing angle of PWM signal. This control scheme is estimated phase and frequency in DQ-transform of PLL controller on time domain. The PLL controllers were locking constant the frequency and voltage of inverter through the signal estimated in DQ-dimension. The proposed methods determine high-precision and accuracy of switching frequency in PLL characteristic based on time domain. Moreover, in this paper represented the 2nd order phase lock loop (PLL) analysis methodology. The 2nd order phase lock loop demonstrated in transfer function form that is measured and analysis the signal in time domain. The close-loop control was analyzed the fast response and stability in frequency domain which is obviously behavior of Phase Lock Loop (PLL). © 2012 ICROS.
Keywords: 9-level diode clamp inverter; Modulation strategy; PLL; Time and Frequency domain